The study of sport manager's decision making styles who are working in Center and Rural Organizations of General Directorate of Sport - Hakan Caglayan; Mustafa Vural (Türk Spor ve Egzersiz Dergisi, 2014)
The present study is conducted in order to determine the effect of demographic variables on decision making styles of sport managers who are working in center and rural organizations of general directorate of sport. A descriptive survey model oriented method is used within the research in order to reveal the present situation. The study group is composed of 170 sport managers working in center and rural organizations of general directorate of sport (Provincial Director of Youth Services and Sport = 32/ Departmental Manager =138). “Melbourne Decision Making Questionaire” which was developed by Mann et al. (1998) and then adapted by Deniz (2004) to Turkish is used as data collection tool along with “Self-Information Form”. While analyzing the data, Mann-Whitney U Test for paired comparison and Kruskal-Wallis Variance Analysis for multiple comparisons are used. In multiple comparisons when Kruskal Wallis Variance Analyses results were found meaningful, Mann Whitney U Test is applied to find out which groups were the sources of the meaningful differences. The significance level in the present study is Î±=0.05. As a result of the study it is found that in terms of gender, age, educational level and managerial status self-esteem has no significant effect on decision making styles of sport managers; however, there was a significant difference regarding professional seniority and managerial seniority variables. It is also seen that there were no significant differences in all the sub-dimensions of decision making scale of sport managers considering the whole demographic variables.